2012
DOI: 10.1021/la301437f
|View full text |Cite
|
Sign up to set email alerts
|

Gel-Based Self-Propelling Particles Get Programmed To Dance

Abstract: We present a class of gel-based self-propelling particles moving by the Marangoni effect in an oscillatory mode. The particles are made of an ethanol-infused polyacrylamide hydrogel contained in plastic tubing. These gel boats floating on the water surface exhibit periodic propulsion for several hours. The release of ethanol from the hydrogel takes place beneath the liquid surface. The released ethanol rises to the air-water interface by buoyancy and generates a self-sustained cycle of surface tension gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 48 publications
1
66
0
1
Order By: Relevance
“…1a-b (the similar construction of the micro-boat was proposed in Ref. 12). Camphor powder and FeCl3 seed crystals were introduced into opposite ends of the tubing, as shown in Fig.…”
Section: Construction Of the Camphor-driven Self-propelling Micro-boatmentioning
confidence: 99%
“…1a-b (the similar construction of the micro-boat was proposed in Ref. 12). Camphor powder and FeCl3 seed crystals were introduced into opposite ends of the tubing, as shown in Fig.…”
Section: Construction Of the Camphor-driven Self-propelling Micro-boatmentioning
confidence: 99%
“…[18,39,40] For this purpose, the molecules often be inserted into as upport, such as gels or metal-organic frameworks (MOFs).…”
Section: Symmetrical Systemsw Ith Spontaneous Symmetry Breakingmentioning
confidence: 99%
“…Also, given the fact that our autonomous hybrid motor is operational at the air-water interface, surfacet ension effects will influence the motor movement (along with the hydrogen evolution reaction as the main propelling mechanism), as observedi nc ase of camphor boats [49,50] and solvent-driven gels. [51] The propulsion concept may draw some parallels to as tudy done by Jin et al, [52] where they demonstrated an ew type of Marangoni propulsion promoting steady velocity for ap rolonged period of time owing to the constant supply of fuel vapor throught he membrane.…”
mentioning
confidence: 93%